A quality improvement study on breast feeding within first hour of caesarean delivery in a tertiary care centre - Pulak Kalita; Pranay Dey; Sweety Begum (Barpeta Obstetrics and Gynaecological Society, 2023)
Objective: To improve the rate of breast feeding within first hour of caesarean delivery over a period of 3 months through quality improvement process. Methods: Baseline rate of breast feeding within first hourof caesarean delivery was measured.Fish bone analysis and Process flow mapping was done to elicit the possible reasons for delay in initiating breast feeding. A series of Plan-Do-Study-Act (PDSA) Cycle was conducted to test change ideas brought forth by forming a team of paediatrician, obstetrician and nurse. Result: The rate of first-hour initiation of breastfeeding increased from 0% to 82% over the study period. The average time at of breastfeeding at the end of PDSA4 was found to be 52 minutes. The results were sustained after the last PDSA cycle. Conclusion: A quality improvement study focussing on health promotion, appropriate intervention and nursing staff's support in providing early skin to skin contact with initiation of breast feeding for patients undergoing caesarean section, was able to accomplish sustained improvement in breastfeeding rates within 1st hour of caesarean deliveries.